Ebrain: The electronic learning platform for clinical neuroscience. (October 2013) - Thomson, S.
Abstract ebrain (www.ebrainjnc.com) is a comprehensive e-learning platform for the clinical neurosciences. It is owned by the Joint Neurosciences Council which is formed from the UK neuroscience specialty associations including the Society of British Neurosurgeons. ebrain has been developed in association with the European Neurology Associations and University College London. The content was written in 2010/11 and the programme was launched in November 2011. It is now one year old. This article reviews the history of the development, its progress since launch, and the plans for the future of this project.